Academic Weariness Of University Displaced Students And Their Counterparts Who Were Returning From Displacement - Mohammed, Aseel Sabbar (International Journal of Psychosocial Rehabilitation, 2020)
The current study is aimed to identify the level of academic weariness and the indication of the differences in the variable on (according to the variable of the displaced and their counterparts who were returning from displacement). in order to achieve the current goal of this research, the researcher has prepared a tool where the academic weariness tool consisted of three fields and (30) paragraphs, after confirming all the psychometric properties of the scale, which were applied to the sample of students, that consisting of (200) male and female students at Anbar University for the academic year (2019-2020), as the results resulted to: • The sample members have enjoyed a high level of academic (weariness) or • There were no indication and statistical differences in the academic weariness between the displaced university students and their returning counterparts from displacement.